Deciphering the distribution of ESKAPE pathogens in various clinical samples and its pattern of antimicrobial resistance: a study from a tertiary care center in Wayanad, Kerala - D. B., Nandhana; Murali, Advaith; B. J., Deepthy (International Journal of Research in Medical Sciences, 2024)
Background: ESKAPE includes 6 nosocomial pathogens which are capable of ‘escaping’ the biocidal actions of antimicrobial agents. Antimicrobial resistance of ESKAPE pathogens in clinical samples is crucial for effective patient management and development of targeted treatment strategy. So, the present study was designed to investigate the distribution of ESKAPE pathogens across diverse clinical samples and to find out their prevalence in different clinical sample such as pus, sputum and urine. This provides an insight to their varied ecological niches within healthcare settings. Methods: This was a retrospective study done at Dr. Moopen’s Medical College. A total of 6492 clinical samples were studied to isolate ESKAPE pathogens. Which included urine, sputum and pus samples. Results: A total of n=6,492 Individual bacteria isolates were recovered from clinical specimens such as sputum (1473), urine (3710) and pus (1309) out of which n=1181 were ESKAPE pathogen. The most frequent clinical sample were pus 580 (49.12%) followed by urine 265 (22.43%) and respiratory samples 336 (28.45%). The most predominant bacteria were found to be Staphylococcus aureus (31.39%) in pus whereas Klebsiella pneumoniae in urine (40.10%) and respiratory samples (40.48%). The average age of the involved patients was approximately 74.8±16.67 years, and the range of ages in the dataset is in 1-97 years, with a gender distribution of 637 (58.28%) males and 470 (42.72%) females. Conclusions: Our findings reveal that pus serves as a significant reservoir for ESKAPE pathogens, with Staphylococcus aureus and Pseudomonas aeruginosa as predominant organisms.